Prevalence and Molecular Characterization of Toxoplasma gondii and Toxocara cati Among Stray and Household Cats and Cat Owners in Tehran, Iran - Karimi, Poorya; Shafaghi-Sisi, Soheila; Meamar, Ahmad Reza; Nasiri, Gelareh; Razmjou, Elham (Frontiers in Veterinary Science, 2022)
Toxoplasma gondii and Toxocara spp. are the most critical parasites common between humans and cats. The close association of cats with humans in urban areas persuaded us to investigate the prevalence of these parasites in stray and household cats and their possible role in the owners' infection. Herein, 132 and 33 fecal samples of stray and household cats, respectively, and 33 blood samples of their owners were collected in Tehran, Iran. The prevalence of T. gondii was determined by targeting the B1 gene in the feces of stray and household cats and the blood of cat owners. Furthermore, genotypes of T. gondii were identified based on the multilocus genotyping of BTUB, GRA6, SAG3, and APICO loci. Toxocara spp. were detected by targeting the second internal transcribed spacer (ITS-2) of the ribosomal DNA of these parasites in the cats' feces and the humans' blood. Also, Toxocara IgG was assessed in the human serum samples. The B1 gene amplification showed that 15.2% of stray cats, 18.2% of household cats, and 51.5% of cat owners were infected with T. gondii. The multilocus sequence analysis revealed the predominance of genotype I of T. gondii in stray cats and genotype II of T. gondii in household cats and cat owners. The amplifying of ITS-2 revealed a high prevalence of T. cati infection (47.0%) in stray cats, whereas no infection was found in the feces of household cats or the serum of cat owners. Likewise, Toxocara IgG was not detected in the serum of humans. The lower prevalence of T. gondii in stray/household cats than in the cat owners indicates the limited impact of close contact with infected cats in human toxoplasmosis. However, the high prevalence of T. cati infection in stray cats can cause contamination of the environment by excreting eggs that may lead to infecting humans through soil or water. Therefore, public health education in urban management planning is necessary for routine urban cat deworming programs and for training the healthcare workers to prevent, control, and treat these infections.